(untitled) (Journal of Health Sciences, 2023)
Introduction: The coexistence of a live fetus in a molar pregnancy is extremely rare and represents a challenge for the maternal-perinatal team. Obstetric aspects have been described previously, but it’s possible effects on the newborn have not been detailed. The case that we present to our knowledge is the first to describe such outcomes. Aim of this case report is to describe the clinical events that occur in a neonate born from the previous coexistence of a molar pregnancy with a live fetus. Case Report: We present the case of a 35-week preterm neonate born by cesarean section due to loss of fetal well-being, who presented with severe intrauterine growth restriction and a high suspicion of intrauterine flow redistribution, with mild hyaline membrane disease. At 48 h after birth, enteral nutrition with infant formula was started in the absence of breast milk, reaching an oral volume of 75 cc/kg/day, after which he presented porraceous residues, abdominal distension, absence of hydroaerial noises, and deterioration. The diagnosis of necrotizing enterocolitis was considered, responding to medical management without the need for a surgical approach. The patient was discharged at 19 days of life with outpatient follow-up. Conclusion: The outcome of complications in a newborn of this rare coexistence is similar to those associated with prematurity and intrauterine growth restriction, the latter being more severe. It is important to focus on the mother-child binomial from the antenatal stage, as well as family-centered care in such a way that modifiable factors such as the degree of acceptance support and availability of autologous milk turn out to be important allies in the context of places with limited resources.